Iranian firms in biopharmaceutical value chain: where to go now?. Issue 1 (19th June 2019) - Afshari-Mofrad, Masoud; Salim, Ali
Abstract : Purpose: Motivated by the huge potential of biosimilars in the near future and rapid growth of Iranian biosimilar producing firms in recent two decades, this paper aims to explore the positioning of these firms in biopharmaceutical value chain and their path of technological capability building to extract policy-relevant advice. Design/methodology/approach: As part of a two-year research project, an online questionnaire was designed and sent to biopharmaceutical experts in Iran between May and October 2016. Respondents came from biopharmaceutical firms. Also, 12 semi-structured interviews were conducted to analyze the path of capability building in Iranian biosimilar-producing firms. Findings: The findings show that Iranian biopharmaceutical firms (BPFs) are mostly concentrated on "pharmaceutical development, ", "drug manufacturing" and " after-sales services' activities." The study also demonstrates that most BPFs in Iran are at the "assimilative" level of capability and a few of them have recently moved toward the "adaptive" level. Originality/value: The findings show that Iranian BPFs are mostly concentrated on "pharmaceutical development, " "drug manufacturing" and "after-sales services" activities. The study also demonstrates that most BPFs in Iran are at the "assimilative" level of capability and a few of them have recently moved toward the "adaptive" level.